Influence of Resources Adequacy on Effectiveness of Audit Committee’s Among Water Authorities in Tanzania - Chindengwike, James (JALOW | Journal of Agribusiness and Local Wisdom, 2026)
An audit committee is important in enhancing the objectivity of financial reporting and internal controls, thus providing further assurances of integrity in government spending. Examined the influence of resource adequacy on the effectiveness of audit committees among water authorities in Tanzania. A survey research design through relationship testing between study variables was employed to generate the data required for the study. Primary data was used to fill the study gap, which was noted from the field through respondents. Primary data were gathered and analysed using the SPSS program to generate the statistics that are presented as the findings of the study. The 100 staff were employed from a population of 335 staff calculated from this study. In particular, both descriptive and inferential statistics were used in the analysis of data using a binary logistic regression model to show the relationship between independent and dependent variables of the study. Financial resources, access to information and frequency of meeting with P-values of 0.019, 0.049 and 0.231, respectively, show all variables are statistically significant except frequency of meeting, while coefficients of financial resources, access to information and frequency of meeting are 0.987, 2.867 and 4.184, respectively. The analysis revealed that there is a positive and statistically significant relationship between audit adequacy of financial and information resources and the effectiveness of the audit committee in compliance with responsibilities as the dependent variables with P < 0.05. The study recommends that resources needed be provided to enable them to perform their duties as required.